2016
DOI: 10.1093/abbs/gmw086
|View full text |Cite
|
Sign up to set email alerts
|

Structure features of GH10 xylanase from <italic>Caldicellulosiruptor bescii</italic>: implication for its thermophilic adaption and substrate binding preference

Abstract: Caldicellulosiruptor bescii is the most thermophilic cellulolytic species of organisms known to date. In our previous study, GH10 xylanase CbXyn10B from C. bescii displayed outstanding hydrolytic activity toward various xylans at high temperatures. To understand the structural basis for this protein's catalysis and thermostability, we solved the crystal structures of CbXyn10B and its complexes with xylooligosaccharides. These structural models were used to guide comparison with its mesophilic counterpart PbXyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…It usually consists of high-molecular weight xylanase with low isoelectric points and displays an (α/β) 8 -barrel fold. This structure mimics the shape of a 'Salad Bowl' , because of an enlarged loop architecture, one face of the molecule is having ~ 45 Å large radius and the other face is having ~ 30 Å radius because of simple (α/β) turns (Zhang et al 2016a(Zhang et al , 2016b. However, these two categories are relatively the same because along with sharing similar fold also shares some common residues and has similar catalytic mechanisms.…”
Section: Mechanism For Glycosidic Hydrolase Family 10 (Gh10)mentioning
confidence: 87%
See 1 more Smart Citation
“…It usually consists of high-molecular weight xylanase with low isoelectric points and displays an (α/β) 8 -barrel fold. This structure mimics the shape of a 'Salad Bowl' , because of an enlarged loop architecture, one face of the molecule is having ~ 45 Å large radius and the other face is having ~ 30 Å radius because of simple (α/β) turns (Zhang et al 2016a(Zhang et al , 2016b. However, these two categories are relatively the same because along with sharing similar fold also shares some common residues and has similar catalytic mechanisms.…”
Section: Mechanism For Glycosidic Hydrolase Family 10 (Gh10)mentioning
confidence: 87%
“…Hence, for complete and efficient hydrolysis of xylan into its constituent sugars requires synergistic action of various enzymes with specifically targeting appropriate bonds of xylan. The multifunction xylanolytic system exists in bacteria (Zhang et al 2016a(Zhang et al , 2016b, fungi (Driss et al 2011;) and actinomycetes (Hunt et al 2016) where xylan backbone is randomly cleaved by the action of endo-1, 4-β-d-xylanases; xylose polymer is broken down to its monomeric form by action of β-dxylosidases. Acetyl and phenolic side branches were removed by the action of α-glucuronidase and acetylxylan esterase.…”
Section: Structure Of Xylan and Role Of Xylanolytic Enzymes In Its Brmentioning
confidence: 99%
“…Xylanases of the GH10 family, which normally have high molecular weight and a (β/α) 8 8-barrel folding structure, hydrolyze xylan through a reservation-type catalytic mechanism (Kim et al 2018;Zhang et al 2016). Crystal structure and dynamics analysis have revealed that these xylanases have four to five active binding sites, and often contain carbohydrate-binding modules (CBM) connected to their catalytic structural domain (Jia and Han 2019; Wu et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The xylanase GH10A is capable of degrading wheat arabinoxylan (WAX) and tamarind xyloglucan and it is difficult to detect the binding ability (Fredriksen et al, 2019). The bifunctional enzymes with xylanase/cellulase activity have been reported such as CbXyn10C (5OFJ) (Chu et al, 2017), SlXyn10A (1E0X) (Ducros et al, 2000a), CbXyn10B (4L4O) (Zhang et al, 2016) and CfCex (Liu, Zhang, & Xu, 2012). CbXyn10C, Xyl10A, and CbXyn10B all have the classic (α/β) 8 TIM-barrel fold structure, but there is no article revealing the "switch" of the GH10 family of xylanases from single function to dual function.…”
Section: Introductionmentioning
confidence: 99%